ANALISIS KAPASITAS YANG TERSEDIA TERHADAP KAPASITAS YANG DIBUTUHKAN DENGAN MENGGUNAKAN METODE RCCP (ROUGH CUT CAPACITY PLANNING) PADA INDUSTRI PULP - Maryam, Maryam; Putra, Hari (Politeknik ATI Padang, 2020)
One of the pulp processing industries in North Sumatra has the basic raw material of the eucalyptus tree. Based on observations in the fiber line department in 2020, there is a difference between the period of required capacity and the period of existing capacity, where the required capacity is greater than the existing capacity. This is because the processing time is quite long and the company's expenditure target is too high. Analysis of existing capacity will be carried out against the required capacity using the RCCP (Rough Cut Capacity Planning) method. The maximum effective output obtained by the company based on the company's current capacity is 139,429 tons and after adding working days the maximum effective output that the company can produce is 186,286 tons. Where after increasing working days the capacity of the company increases. The solution to achieve the capacity required by the company is to work overtime, subcontract with other companies, adjust the production plan by reducing the production target according to the existing capacity period, carry out scheduled machine maintenance, and in the long run, replace the machine during washing. and workstations for refining, bleaching and pulping machines.